Cross–asset class portfolio between gold and stocks in Indonesia - Mesakh Prihanto Surya Putra; Apriani Dorkas Rambu Atahau; Robiyanto Robiyanto (Universitas Islam Indonesia, 2018)
This study observes the effectiveness of hedging by using the gold commodity futures instrument as a hedge asset towards Indonesian stock which is represented by sectoral indices and Composite Stock Price Index (CSPI). By using DCC-GARCH which can dynamically accommodate the correlation between gold and the stock, this study found gold could become a safe haven asset towards stock in Indonesia. In addition, this study found that gold can effectively become a hedge asset for the stocks in Indonesia and the hedged portfolio resulted in a higher risk-adjusted performance of the portfolio of investment.